PENGARUH LINGKUNGAN KERJA DAN PELATIHAN KERJA TERHADAP MOTIVASI KERJA YANG BERDAMPAK PADA KINERJA GURU - Rahmat Setiabudi; Muhammad Alfi Alhubbufillah (Program Studi Ekonomi Syariah, 2023)
This research is motivated by problems that exist in the school environment such as poor working relations between teachers causing a lack of comfort at work, lack of teacher skills in improving teaching competencies so that it affects work initiatives and will have an impact on teacher performance. This study aims to analyze: 1) To determine the effect of the work environment on work motivation at SMK Korwil Kemang, Parung District. 2) To find out the effect of the work environment on work motivation at SMK Korwil Kemang, Parung District. 3) To determine the effect of the work environment and job training simultaneously on work motivation at SMK Korwil Kemang, Parung District. 4) To find out the effect of work motivation that has an impact on teacher performance at SMK Korwil Kemang, Parung District. The method in this study is associative with a quantitative descriptive approach. The population and sample in this study were 100 respondents and used a saturated sampling technique to determine the number of samples. The analysis tool uses multiple linear regression analysis and simple linear regression analysis with the help of SPSS 23 software. The results of the study show that there is a significance value of 0.000 less than 0.005 or Sig 0.000 <0.05. So from the above results it can be concluded that: the independent variable, namely the Work Environment (X1) has an effect on Work Motivation (Y), Job Training (X2) has an effect on Work Motivation (Y), Work Environment (X1) and Job Training (X2) together have an effect on Work Motivation (Y), and Work Motivation (Y) have an impact on Teacher Performance (Z)